2015
DOI: 10.1194/jlr.m057679
|View full text |Cite
|
Sign up to set email alerts
|

Foxc2 enhances proliferation and inhibits apoptosis through activating Akt/mTORC1 signaling pathway in mouse preadipocytes

Abstract: found in various organs and tissues, such as the cardiac system, mammary gland, liver, and adipose tissue . In general, Foxc2 plays important roles in the regulation of cell growth, proliferation, differentiation, apoptosis, and energy metabolism. Mice lacking Foxc2 die during embryogenesis or perinatally and exhibit aortic arch and skeletal defects ( 1-4 ). Previous studies have shown that, in adipocytes, either a high-calorie diet or insulin induces Foxc2 expression, suggesting that Foxc2 is an important met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 51 publications
2
37
1
Order By: Relevance
“…The molecular mechanism behind this correlation was shown to be that FOXC2 downregulates p120-catenin, which directly suppresses the promoter activity of E-cadherin [21]. FOXC2 has been reported to enhance AKT activity to promote cell proliferation and invasion [13, 22, 23]. In our study, we found that FOXC2 is upregulated in HCC tissues and that high FOXC2 expression is correlated with poor prognosis, suggesting that FOXC2 contributes to the acquisition of the aggressive properties of HCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanism behind this correlation was shown to be that FOXC2 downregulates p120-catenin, which directly suppresses the promoter activity of E-cadherin [21]. FOXC2 has been reported to enhance AKT activity to promote cell proliferation and invasion [13, 22, 23]. In our study, we found that FOXC2 is upregulated in HCC tissues and that high FOXC2 expression is correlated with poor prognosis, suggesting that FOXC2 contributes to the acquisition of the aggressive properties of HCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies found Foxc2 enhanced mice pre-adipocytes proliferation and inhibited apoptosis via activating Akt/mTORC1 signaling pathway23. Foxc2 stimulates osteogenic differentiation and inhibits adipogenic differentiation in bone marrow mesenchymal stem cells, and in white adipocytes2425.…”
mentioning
confidence: 93%
“…The activation of Akt facilitates growth factor-mediated cell survival by inhibiting apoptosis via the phosphorylation and inactivation of various pro-apoptotic signals including Bcl-2-associated death (BAD) [5] and Forkhead box O (FOXOs) [6, 7], and promotes cell proliferation by phosphorylation and inhibition of the tumour suppressor tuberous sclerosis complex 2 (TSC2) and the activation of mammalian target of rapamycin complex 1 (mTORC1) [8, 9]. Additionally, it has been reported that Akt is also involved in the activation of various oncogenic signalling pathways such as Nuclear factor kappa B (NF-κB), c-myelocytomatosis (c-Myc), Vascular endothelial growth factor (VEGF) and Cyclin D, thus acting as a central regulator of various cellular functions including cell growth, survival, and metabolism [10].…”
Section: Introductionmentioning
confidence: 99%